1974
DOI: 10.1128/am.28.4.618-622.1974
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Salmonella with the O-1 Bacteriophage

Abstract: The O-1 bacteriophage test of Cherry et al. (1954) for the presumptive identification of salmonellae in the diagnostic laboratory was investigated. A phage lysate with a titer of 10 12 plaque-forming units per ml was found to be optimal. This preparation lysed 98.2% of Salmonella strains tested, while maintaining its high specificity for salmonellae. Gram-negative organisms other than salmonellae were resistant to the O-1 phage; however, 5.9% of Esche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In 2011, it was classified as the type species of the Felixounavirus genus proposed by the ICTV [14]. Importantly, phages of Felixounavirus genus have been shown to infect several different types of Salmonella serovars [15,16]. Further reports of phages of the Felixounavirus genus have shown their potential for infecting Salmonella of numerous serovars, including descriptions of isolations from several countries such as Russia, the United States, and Chile, which were recovered in samples from different sources: chicken and bovine feces, sewage, and farm soil [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, it was classified as the type species of the Felixounavirus genus proposed by the ICTV [14]. Importantly, phages of Felixounavirus genus have been shown to infect several different types of Salmonella serovars [15,16]. Further reports of phages of the Felixounavirus genus have shown their potential for infecting Salmonella of numerous serovars, including descriptions of isolations from several countries such as Russia, the United States, and Chile, which were recovered in samples from different sources: chicken and bovine feces, sewage, and farm soil [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Kentucky. Bacteriophage Felix 01 is a good example of a wide host range; it lyses nearly 98.5% of the tested Salmonella ( Welkos et al, 1974 ). However, using a phage cocktail might solve the limitation of a narrow host range bacteriophages.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that phage LPSent1 had a robust lytic activity with a wide host range against several strains of S. Enteritidis, S. Typhimurium and S. Kentucky. Bacteriophage Felix 01 is a good example of a wide host range; it lyses nearly 98.5% of the tested Salmonella (Welkos et al, 1974). However, using a phage cocktail might solve the limitation of a narrow host range bacteriophages.…”
Section: Host Rangementioning
confidence: 99%